MENINGKATKAN KEMAMPUAN BERBICARA SISWA TK MENGGUNAKAN METODE BERMAIN PERAN - Julianti; Asep Saepurokhman; Nurul Alif Hanif; Ani Hernawati; Risa Marini Yonita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Speaking ability is an essential skill that must be developed in early childhood because it influences social interaction and learning achievement. Initial observations at TK BPP Rendakasih, Cisitu District, showed that some students were still passive and lacked confidence in speaking, indicating the need for a learning strategy that could increase participation and verbal skills. This study aims to analyze the effect of role-playing methods on students’ speaking ability and to improve teacher and student activity during learning. The research employed Classroom Action Research (CAR) with the Kemmis and McTaggart spiral design, consisting of four phases: planning, acting, observing, and reflecting. The research subjects were students of Group B at TK BPP Rendakasih, conducted over three cycles with one meeting per cycle. Data were collected through observation of teacher activity, student participation, and speaking ability tests, then analyzed descriptively both qualitatively and quantitatively to observe trends of improvement across cycles. The results showed significant improvements in all three aspects: teacher activity increased from 62% to 100%, student activity increased from 53% to 87%, and students’ speaking ability improved from 52% to 88%, indicating that the role-playing method effectively encourages engagement, confidence, and verbal skills. In conclusion, the role-playing method is proven to enhance early childhood speaking skills comprehensively and improve learning quality. It is recommended that teachers continue implementing role-playing strategies with varied media and ongoing evaluation, while adjusting roles and activities according to students’ characteristics for optimal results. Keywords: role-playing, speaking ability, early childhood, classroom action, learning